Pseudomonas Inoculation Stimulates Endophytic Azospira Population and Induces Systemic Resistance to Bacterial Wilt - Shang, Xian-chao; Cai, Xianjie; Zhou, Yanan; Han, Xiaobin; Zhang, Cheng-Sheng; Ilyas, Naila; Li, Yiqiang; Zheng, Yanfen (Frontiers in Plant Science, 2021)
Bacterial communities in the rhizosphere play an important role in sustaining plant growth and the health of diverse soils. Recent studies have demonstrated that microbial keystone taxa in rhizosphere microbial community are extremely critical for the suppression of diseases. However, the mechanisms involved in the disease suppression of keystone species remain unclear. The present study assessed the effects of three Pseudomonas strains, which were identified as keystone species in our previous study, on the growth performance and root-associated bacterial community of tobacco plants. A high relative abundance of Ralstonia was found in the non-inoculated group, while a large Azospira population was observed in all groups inoculated with the three Pseudomonas strains. Correspondingly, the activities of the defense-related enzymes and the expression levels of the defense signaling marker genes of the plant were increased after inoculating the Pseudomonas strains. Moreover, the correlation analyses showed that the relative abundance of Azospira, the activity of superoxide dismutase (SOD), catalase (CAT), and polyphenol oxidase (PPO), and the expression of H1N1, ACC Oxidase, and PR1 a/c had a significantly negative (P < 0.05) relationship with the abundance of Ralstonia. This further revealed that the keystone species, such as Pseudomonas spp., can suppress bacterial wilt disease by enhancing the systemic resistance of tobacco plants.